Hot subdwarfs in binary systems and the nature of their unseen companions - Geier, Stephan; Heber, Ulrich; Tillich, A.; Hirsch, H.; Edelmann, Heinz; Schaffenroth, Veronika; Kupfer, Thomas; Mueller, S.; Maxted, P. F. L.; Ostensen, R.; Podsiadlowski, P.; Marsh, T.; et al. (Astrophysics and Space Science, 2010)
A large fraction of the sdB stars reside in short period binaries. It is therefore clear that binary evolution plays an important role in the still unsolved problem of hot subdwarf formation. Here we present new results from different projects devoted to the analysis of sdBs in close binaries. The nature and masses of the unseen companions of 31 sdBs have been constrained by an analysis of high resolution spectra. In the course of this study candidate systems with massive compact companions have been discovered. The HYPERMUCHFUSS project aims at finding such systems making use of the huge spectral database of SDSS. A multi-site follow-up campaign of promising radial velocity variable sdBs started in 2009 and preliminary results are shown here. The most recent discovery of a substellar companion to the bright sdB HD 149382 may provide new evidence for the decisive role of low mass companions for sdB formation in general. A mysterious IR-excess has been detected, which may be caused by this otherwise invisible companion. Another low mass companion has been found to orbit the sdB star EGB 5 within 16.5 days. The space mission CoRoT is performing wide field and high precision photometry. First preliminary results from a spectroscopic survey of the COROT fields are also reported.
Keywords: Stars: horizontal branch; Stars: binaries